ChemInform Abstract: Nickel‐Catalyzed Addition‐Type Alkenylation of Unactivated, Aliphatic C—H Bonds with Alkynes: A Concise Route to Polysubstituted γ‐Butyrolactones. Issue 40 (October 2015) - Li, Mingliang; Yang, Yudong; Zhou, Danni; Wan, Danyang; You, Jingsong
Abstract The β‐C(sp3)—H bonds of aliphatic amides containing a quinolinyl group [e.g. (I)] are activated by nickel through a chelation.